Implementation of the educational process in the course of contact extracurricular work with students - Anna L. Morozova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article presents a substantial analysis of the Federal state educational standards (undergraduate and graduate level), implemented in the educational process of educational organizations subordinated to the Federal penitentiary service, in order to clarify the directions of the educational process of students in the framework of contact extracurricular work. The presented directions of educational work with cadets of departmental educational organizations are aimed at the development of moral, mental, labor and civil-patriotic education of students in accordance with the results of training (competencies) identified in the analyzed FSES. The author views the question of universality of the specified directions of educational work with the studying departmental educational organizations in the declared directions of preparation and specialties. The main aspects of the implementation of the educational process in the course of contact extracurricular work with cadets of departmental educational organizations of the penitentiary service of Russia are studied here, including the example of the discipline "Foreign language" and work with extracurricular reading. The discipline "Foreign language" has an extensive educational potential due to: expansion of ideas of students about the possibilities of using a foreign language in the professional sphere; formation of General cultural competences of students, improvement of skills and abilities to use the received ideas and knowledge in direct and indirect professionally-oriented foreign language communication; formation of professional competence of students. The author touches upon the problem of using the concept in the educational process. In particular, the author analyzes the concept of "punishment". Also the author accumulated pedagogical experience of realization of the concept "punishment" educational potential during contact extracurricular work on discipline "Foreign language". Conceptualization of the concept "punishment" is achieved by communicative basis of contact extracurricular work and carrying out linguistic and cultural mini-research of the word form of punishment itself and drawing up its associative verbal network.